The miR164a targets CsNAC1 to negatively regulate the cold tolerance of tea plants (Camellia sinensis) - Siya Li; Lu Cao; Ziwen Zhou; Yaohua Cheng; Xianchen Zhang; Yeyun Li (Journal of Integrative Agriculture)
Cold stress widely impairs the quality and yield of tea plants. The miR164 family and its target NAC transcription factor have been identified as crucial regulators in response to cold stress. However, the role of miR164 and CsNAC in cold tolerance in tea plants was little understood. In our study, the expression level of CsMIR164a was significantly reduced under cold stress and significantly and negatively correlated with that of CsNAC1. 5´ RACE and GUS histochemical assays showed that CsNAC1 was cleaved by CsMIR164a. The CsMIR164a-silenced tea leaves promoted the expression levels of CsNAC1 and CsCBFs and exhibited greater cold tolerance. Also, the overexpression of CsNAC1 enhanced cold tolerance in transgenic Arabidopsis plants by promoting the expression levels of AtCBFs. In contrast, the heterologous overexpression of CsMIR164a in Arabidopsis decreased the expression level of AtNACs and AtCBFs and thus impaired cold tolerance. Additionally, silencing of CsNAC1 impaired the expression levels of CsCBFs, resulting in greater cold sensitivity in tea leaves. Our present study demonstrated that the miR164a-CsNAC1 module may play a negative role in the cold tolerance of tea plants via the CsCBF-dependent pathway.